(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2013)
The level of the gross premium is continuously climbingin the non-life industry. Over the years, the public sector insurers contributemaximum premium value to non-life business than the private sector insurers.But considering the growth level, the private sector insurers have been showingtremendous growth rate year on year. During the financial year 2007-08, thenon-life industry had two new entrants in the private sector, namely,Cholamandalam General Insurance and HDFC Chubb General Insurance. The publicsector Export Credit and Guarantee Corporation (ECGC) got itself registeredwith the IRDA in the year 2007-08. In the financial year 2004-05, the growthrate of both the sectors is tremendously high (public-13.59% and private-6904.96%), but in the year 2005-03,6the premium volume declines with a muchhigher growth rate in both the sectors (public- 5.57% and private 193.43%) ascompared to previous year. Thereafter, the growth rate of established insurersis keep on fluctuating up and down whereas the growth rate of private insurersis on the rise every year.